Morphometric Study of Sacral Hiatus: A Basis for Successful Caudal Epidural Block - Pal, Diplani Rani; Rahman, Md. Ashfaqur; Fatema, Kanij (Bangladesh Journal of Anatomy, 2013)
Bangladesh Journal of Anatomy, January 2012, Vol. 10 No. 1 pp 5-10 DOI: http://dx.doi.org/10.3329/bja.v10i1.15750